Green Synthesis of Nanocomposite of Ag/Ag2O Using Coelomic Liquid: Optical Absorption Analysis - Esmaeil Shahriari; Morteza Raeisi; Karim Aliakbari (Nanochemistry Research)
In this research, silver and silver oxide (Ag/Ag2O) nanocomposites were synthesized using a green method at different concentrations of silver nitrate. In this method, coelomic yellow liquid extracted from earthworms was used as a silver nitrate reduction, which was the novelty of the present work. The obtained nanoparticles crystal structure was analyzed by X-ray diffraction pattern and the Rietveld method. Results showed that with increasing the silver nitrate concentration, size and strain of silver oxide nanoparticles remained unchanged, but the silver nanoparticles size increased while strain decreased. SEM images indicated uniform particle distribution, high density, and spherical geometric shape, and their average size changes in the range of 23 ≤ λ ≤ 63 nm By measuring and fitting the nanocomposites ultraviolet (UV) spectra, weight percentage, and absorption peak of each component were determined. Accordingly, with increasing the silver nitrate concentration, the absorption peak for silver nanoparticles shifted to the higher wavelengths, and for silver oxide nanoparticles this peak remained almost constant. Also, silver oxide weight percentage remained almost constant and increased for silver nanoparticles. In the framework of a simple kinematic model, it is shown that its origin can be related to the different reaction speeds of the silver nitrate conversion to Ag/Ag2O.